Kolaborasi Pemerintah Desa Kalukubodo Kec. Galesong Selatan Kab. Takalar dan Perguruan Tinggi Stia Yappi Kita Wujudkan Kemandirian Lokal dan Ketahanan Pangan - Nurasia Natsir; Indriati Amirullah; Syafaruddin Syafaruddin; Khaeriyah Khaeriyah; Mursalin Mursalin; Muhammad Natsir Mallawi (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Community Service Activities (PKM) carried out by the STIA YAPPI LECTURER TEAM in collaboration with the Kalukubodo Village Government, South Galesong District, Takalar Regency, aims to increase local independence and food security in the area. This research explores collaboration between the two parties in designing and implementing programs that support sustainable agricultural development. By utilizing the potential of abundant natural resources, this activity includes training in agricultural techniques, use of technology, and effective natural resource management. The results of this activity show that the community's active participation in the training program increases their knowledge and skills, so they are able to optimize local resources to meet food needs independently. In addition, this collaboration also creates sustainable relationships between village governments and universities, opening up opportunities for innovation in resource management. It is hoped that this research can make a significant contribution to the development of models of local independence and food security in other villages in Indonesia.